Student Attendance Information System at SMKN with Web-Based QR Code - Rojari, Fatima; Kelen, Yoseph Pius Kurniawan; Syarifuddin, Risald; Fallo, Kristoforus; Syahyadi, Asep Indra (JESII: Journal of Elektronik Sistem InformasI, 2025)
SMKN Kakuluk Mesak is a vocational high school located in Dua Laus Village, Kakuluk Mesak District, Belu Regency, East Nusa Tenggara Province, which prepares students to work in specific fields. Students can continue their education at SMK after completing their education at the junior high school level. The study period for SMK students is carried out for three to four years of learning, which is divided into three years of study at school and one year in the related industry department. SMKN Kakuluk Mesak has five majors: APAT, NKPI, WBE, TKPI, and APHPI. One of the problems at SMKN Kakuluk Mesak in terms of technology is the manual attendance and grading of students. Attendance and grades are recorded using books. Therefore, a web-based student attendance information system with QR code is needed to facilitate the student attendance process. This system is built using the waterfall method, which is a systematic and directed approach to developing software in which it is used step by step until it runs in order. This research resulted in a website-based student attendance information system with QR code that helps the school manage attendance data and students can view grades and attendance records anytime and anywhere. Keywords: Website; QR Code; Attendance; Waterfall